Development of a Social Contact Survey Instrument Relevant to the Spread of Infectious Disease and Its Application in a Pilot Study Among Korean Adults - Hyang Soon Oh; Youngran Yang; Mikyung Ryu (Journal of Preventive Medicine and Public Health, 2020)
Objectives This study aimed to develop a valid social contact survey instrument and to verify its feasibility for use among Korean adults. Methods The Delphi technique was used to develop an instrument to assess social contacts, which was then applied in a cross-sectional pilot study. A panel of 15 medical professionals reviewed the feasibility and validity of each item. The minimum content validity ratio was 0.49. Thirty participants used the developed measure to record contacts during a 24-hour period. Results After a systematic review, the survey instrument (parts I and II) was developed. Part I assessed social contact patterns over a 24-hour period, and part II assessed perceptions of contacts in daily life and preventive behaviors (hand hygiene and coughing etiquette). High validity and feasibility were found. In the pilot study, the 30 participants had a combined total of 198 contacts (mean, 6.6 daily contacts per person). The participants’ age (p=0.012), occupation (p<0.001), household size (p<0.001), education (p<0.001), personal income (p=0.003), and household income (p<0.001) were significantly associated with the number of contacts. Contacts at home, of long duration, and of daily frequency were relatively likely to be physical. Assortative mixing was observed between individuals in their 20s and 50s. Contact type differed by location, duration, and frequency (p<0.001). Conclusions The developed social contact survey instrument demonstrated high validity and feasibility, suggesting that it is viable for implementation.